Pengembangan Masyarakat: Merancang Media Pembelajaran yang Efektif dan Efisien Bagi Guru di Masa Pandemi Covid-19 - Nadya Fadillah Fidhyallah; Susan Febriantina; RR. Ponco Dewi Karyaningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The Covid-19 pandemic, which has spread throughout the world, has had a significant impact on various sectors, one of which is the education sector. Schools must ensure to continue the learning process even though in any difficult and limited situations. Based on the interviews, observations, data analysis, and identification of the problems, we found some problems relates to these; suddenly changes to new learning models (school from home) caused by Covid-19 Pandemic, the lack of teacher’s competence in designing creative instructional media, and the lack of teacher’s training in designing media learning. Thus, teachers are required to design effective and efficient learning media as creative and innovative distance learning. This community service aims to help vocational teachers in Jakarta, Bogor, Depok, Tangerang, and Bekasi improve their competence and skills by designing effective and efficient PowerPoint as a learning media. This activity is designed through a webinar with a zoom application.